Homologous recombination deficiency as an ovarian cancer biomarker in a real-world cohort: validation of decentralized genomic profiling - Denkert, Carsten; Romey, Marcel; Swedlund, Brad; Hattesohl, Akira; Teply-Szymanski, Julia; Kommoss, Stefan; Kaiser, Kristin; Staebler, Annette; du Bois, Andreas; Grass, Albert; Knappmeyer, Christiane; Heitz, Florian; et al. (The journal of molecular diagnostics, 2022)
The diagnostic evaluation of homologous recombination deficiency (HRD) is central to define targeted therapy strategies for patients with ovarian carcinoma. We evaluated HRD in 514 ovarian carcinoma samples by next-generation sequencing of DNA libraries, including BRCA1/BRCA2 and 26,523 single-nucleotide polymorphisms using the standardized Myriad HRD assay, with the predefined cut point of ≥42 for a positive genomic instability score (GIS). All samples were measured in the central Myriad laboratory and in an academic molecular pathology laboratory. A positive GIS was detected in 196 (38.1%) of tumors, whereas 318 (61.9%) were GIS negative. Combining GIS and BRCA mutations, a total of 200 (38.9%) of the 514 tumors were HRD positive. A positive GIS was significantly associated with high-grade serous histology (P < 0.000001), grade 3 tumors (P = 0.001), and patient age <60 years (P = 0.0003). The concordance between both laboratories for the GIS status was 96.9% (P < 0.000001), with a sensitivity of 94.6% and a specificity of 98.4%. Concordance for HRD status was 97.1% (499 of 514 tumors). The percentage of HRD-positive tumors in our real-life cohort was similar to the proportion observed in the recently published PAOLA-1 trial, with high concordance between central and local laboratories. Our results support introduction of the standardized HRD assay in academic molecular pathology laboratories, thus broadening access to personalized oncology strategies for patients with ovarian cancer worldwide.